Non-conventional Ce:YAG nanostructures via urea complexes - Armetta, Francesco (Sci Rep, 2019)
Ce:YAG nanostructures (Ce:YAG = Cerium in Yttrium Aluminium Garnet), easy to control and shape, have been prepared via templating approach using natural and synthetic materials (i.e. paper, cotton wool and glass wool) previously soaked with a gel-like metals precursor and then thermally treated to achieve the wished morphology. The final material, otherwise difficult to process, can be easily moulded, it is lightweight, portable and forms, at the nanoscale, homogeneous layers of interconnected but not agglomerated nanoparticles (15 ± 5 nm). Using the same synthetic route, called Urea-Glass-Route, but in absence of a template, extremely pure Ce:YAG nanoparticle (45 ± 5 nm) can be also prepared, highly crystalline and well-defined in size and shape. Both structural and optical properties of the final materials were investigated, showing high optical quality. The support allows the production of a multifunctional material with mouldable shape and potential lighting application for large structures combining the strength, chemical durability, fire resistance, and translucency of glass fibres. Last, but not least, the synthetic path also allows an easy scaling up of the process: the first, key step for practical application of nanosized rare-earth doped YAG on large scale.